MEMPERTAHANKAN IMAN DITENGAH ANCAMAN - Harijo y Budisulistyo, MA.; kori P (FILADELFIA: Jurnal Teologi dan Pendidikan Kristen, 2021)
Maintaining faith when becoming a Christian is not an easy thing, especially when experiencing persecution, life is threatened, and so on, minority Christians will experience tremendous pressure when they are in a society where the majority do not know and believe in Jesus Christ, that's how experienced by the church in Pergamum. Based on the following interpretation, it may be helpful to learn what events occurred at that time.